Discrete-time preview control problem in finite horizon - Wang, Hongxia (2014)
This paper considers the H ∞ preview control problem for discrete-time systems. It investigates the problem via game theory and dynamic programming. Different from the existing results, on one hand, the proposed approach is suitable for dealing with the corresponding multiple preview channels problem; on the other hand, the approach provides a possibility in explaining how the preview controller improves the H ∞ performance and why the performance will be saturated.